Penerapan Asas Sidang Terbuka untuk Umum dalam Penyelesaian Perkara Perdata Melalui E-COURT - Dina Yaniar Putri; Moh. Ali Hofi (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
E-Court is a court instrument in seeking legal certainty so that cases can be resolved quickly. The scope of E-court includes online case registration (e-filling), online estimation of case costs (e-skum), online payment of downpayment (e-payment), online summons of parties (e-summons) and online hearings (e-litigation) by sending court documents (Replik, Duplik, Conclusion, Answer). The focus that will be discussed in this scientific work includes first, how to read the judge’s decision via E-court. Second, how to apply the principle of hearings open to the public via E-court. To facilitate understanding in this research, researchers used a Normative Juridical research method with a Legislative approach. The data colletion technique carried out by the researcher was by identifying and analyzing statutory regulations, namely PERMA Number 1 Of 2019. The results of the research carried out by the researcher can be concluded that first, the application of the principle of open to the public hearings is appropriate and reflects the applicable statutory regulations. And will still be implemented, but with several restrictions on the number of court visitors and the distance between visitors. Second, regarding the reading of the judge’s decision via e-court, it is legally considered to have been attended by the parties and carried out in a trial open to the public. And has legal force and legal consequences.